Salivary IgA and periodontal treatment needs in diabetic patients - Luciana Salles Branco-; Cláudia Maria Coêlho Alves; Fernanda Ferreira Lopes; Adriana de Fátima Vasconcelos Pereira; Rosane Nassar Meireles Guerra; Antônio Luiz Amaral Pereira (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Salivary IgA can serve as a first line of defense against pathogens that colonize and invade mucosal surfaces and may be protective against periodontal disease. The aim of this study was to assess salivary immunoglobulin A levels in diabetic and non-diabetic patients with different periodontal treatment needs. The Periodontal Screening & Recording (PSR) system was used to evaluate the periodontal treatment needs of 41 diabetic and 42 non-diabetic patients. Unstimulated whole saliva was collected from each patient immediately before clinical examination and stored at -20 °C until analysis. Salivary immunoglobulin A (s-IgA) levels were determined using an enzyme-linked immunosorbent assay, and values were expressed as optical density. Diabetic and non-diabetic patients were compared using clinical and laboratory data. PSR data indicated that periodontal disease was more frequent and more severe in diabetic patients. A higher prevalence of codes 3 and 4 was observed in diabetics as compared with non-diabetics (odds ratio = 2, P < 0.05). Furthermore, non-diabetic patients had more healthy sextants (code 0) than did diabetic patients. Over half of diabetic patients (∼54%) presented with s-IgA levels that were lower than the normal range (optical density from 0.4 nm to 0.6 nm; P < 0.05). In addition, diabetic patients showed a higher variability in s-IgA levels as compared with non-diabetic patients. In conclusion, diabetic individuals had lower s-IgA levels, more-frequent and more-severe periodontal disease, and a greater need for periodontal treatment as compared with non-diabetic patients.